Incision pressing, a simple and effective intervention to reduce colorectal surgical site infection: A propensity score-matched study - Jiang, Yugang; Chen, Hongyuan; Liu, Guotao; Liu, Meifeng; Kong, Meng; Sheng, Hongguang (Frontiers in Surgery, 2022)
Background: Colorectal surgery is associated with a high risk of surgical site infection (SSI). In March 2017, we developed an intervention, called “PRESS”, with the aim of reducing colorectal superficial SSI. This study assessed the effect of the new intervention in reducing the rates of superficial SSI in colorectal surgery. Methods: This study was a retrospective review of 312 PRESS+ patients compared to 171 historical control PRESS- patients who were 18 years of age or older and underwent elective colorectal surgery with clean-contaminated wounds from January 2015 to June 2020. In the PRESS+ groups, we pressed the incision downward hard with clean gauze after the interrupted suturing of the skin. Propensity score matching with 15 variables was performed in a 1:1 ratio to reduce selection bias. Univariate analysis and multivariate analysis were performed to identify risk factors associated with SSI. Results: The characteristics of the PRESS+ (n=160) and PRESS- (n=160) groups were well balanced after propensity score matching. The PRESS+ group had a lower superficial SSI rate (1.9% vs. 6.9%, P = 0.029) and a lower overall SSI rate (2.5% vs. 10.0%, P = 0.006) than the PRESS- group. Furthermore, multivariate analysis showed that the incisional press was an effective protective factor for superficial SSI (adjusted odds ratio = 0.215, 95% confidence interval = 0.057-0.818, P = 0.024). In addition, female sex (P = 0.048) and blood transfusion (P = 0.011) were demonstrated to be independent risk factors for superficial SSI. Conclusion: The incisional press after suturing is a simple, costless, and effective intervention in reducing superficial incisional SSI.